ANALISIS PERBANDINGAN PEMBAYARAN TUNAI DAN QRIS (STUDI KASUS: CORAK COFFEE) PERIODE 2022–2025 - Toataubun, Warda; Muchran, Muchriana; Salam, Abd (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to compare the use of cash and Quick Response Code Indonesian Standard (QRIS) payment methods on sales at the Corak Coffee MSME during the period 2022–2025. This study uses a comparative quantitative approach, utilizing secondary data in the form of monthly sales reports. Data collection was conducted through documentation, while data analysis was performed using SPSS application through descriptive analysis, normality tests, ANOVA tests, and the Wilcoxon Signed Rank Test. The results show that, on average, sales through QRIS (mean = Rp5,494,943.75) are higher than cash payments (mean = Rp4,609,139.58). The ANOVA test yielded a significance value of 0.027, indicating a statistically significant difference in the average value between the two payment methods at the α = 0.05 level. However, the Wilcoxon Signed Rank Test yielded a significance value of 0.145, indicating that the difference is not statistically significant using the non-parametric approach. This means that although QRIS tends to generate higher sales values, its use has not shown a significant difference compared to cash payments when assessed non-parametrically. Thus, QRIS has become a potential payment alternative for MSMEs, although cash payments still play an important role in daily transaction activities.